2021
DOI: 10.1155/2021/5527292
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Ischemia Onset Based on Automatically Generated Spectralis SD-OCT Values in Acute Central Retinal Artery Occlusion

Abstract: Acute central retinal artery occlusion (CRAO) induces a time-dependent increase in retinal thickness. By manually measuring the relative retinal thickness increase (RRTI) in comparison to the contralateral eye based on optical coherence tomography (OCT), ischemia onset within the past 4.5 hours could be determined with 100% sensitivity and 94.3% specificity. To enable examiner-independent and quicker diagnostics, we analyzed the RRTI using the automatic retinal thickness measurement. In this retrospective stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 17 publications
1
10
0
Order By: Relevance
“…After the REVISION-Trial, data on the robustness of the questionnaire will be available. Furthermore, as the REVISION-Trial will be investigating the biomarkers observed in ocular coherence tomography (14,17), it should be possible to diagnose CRAO without fundoscopy in the future. Diagnosing CRAO without fundoscopy would be especially important in stroke units, which frequently lack the ophthalmologist expertise to confirm CRAO, keeping in mind that the effectivity of IVT seems to be extremely time-dependent (9,10).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After the REVISION-Trial, data on the robustness of the questionnaire will be available. Furthermore, as the REVISION-Trial will be investigating the biomarkers observed in ocular coherence tomography (14,17), it should be possible to diagnose CRAO without fundoscopy in the future. Diagnosing CRAO without fundoscopy would be especially important in stroke units, which frequently lack the ophthalmologist expertise to confirm CRAO, keeping in mind that the effectivity of IVT seems to be extremely time-dependent (9,10).…”
Section: Discussionmentioning
confidence: 99%
“…Over half of the stroke units in Germany (51.9%) reported a lack of ophthalmologic expertise (13). Furthermore, fundoscopic anomalies, such as a cherry red spot or visible retinal pallor, may be lacking within the first hours after symptom onset (9), which is why alternative diagnosing tools and biomarkers for retinal ischemia are being investigated (14)(15)(16)(17)(18)(19). All diagnosing tools not involving fundoscopy may enhance the chances of CRAO patients being treated within 4.5 h after symptom onset.…”
Section: Enzo Maria Vingolo Sapienza University Of Rome Italymentioning
confidence: 99%
“…Administration of IVT within 4.5 h shows a superior visual prognosis compared to the untreated natural course ( 4 , 6 , 7 ). The RRTI, the change of retinal thickness in the affected compared to the healthy fellow eye, is a parameter showing temporal changes and therefore allowing a highly accurate estimate of ischemia duration, which can be essential when the exact onset of symptoms cannot be reported reliably ( 10 , 16 , 17 ). Furthermore, the RRTI might reveal the amount ischemia induced retinal damage (higher RRTI represents more severe damage).…”
Section: Discussionmentioning
confidence: 99%
“…Several retinal ischemia biomarkers can be visualized early, using OCT imaging within the acute phase of CRAO. Besides a loss of structure of the retinal layers, ischemic intracellular edema causes a time-dependent increase in retinal thickness, which eventually resolves and is followed by severe inner retinal atrophy in the chronic phase ( 9 , 10 , 12 , 14 – 18 ). The relative retinal thickness increase (RRTI, retinal thickness increase at the thickest portion of the papillomacular bundle of the affected compared to unaffected eye) may provide information about the onset of ischemia with high accuracy ( 16 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation